Study of factors associated with waiting time for patients undergoing emergency surgery in a tertiary care centre in Nepal - Acharya, Subhash Prasad; Dharel, Dinesh; Upadhyaya, Smrity; Khanal, Nabin; Dahal, Sandesh; Dahal, Sumit; Aryal, Karmapath (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Emergency surgeries throughout the world are demanding earlier surgical times. In a developing country like Nepal this cannot be possible because of lot of factors. So we planned to study such factors that could interplay and increase the waiting time for emergency surgeries. Methods: A prospective observational study was conducted over 45 days and all patients diagnosed with general surgical and orthopedic emergencies were followed till they were operated. Results: Out of 1211 patients presenting to emergency department, 92 required emergency surgery. The mean age was 29.72 year and 76.1% of the patients were male. The mean time from presentation to the emergency department to the first surgical consultation was 170 minutes, from surgical consultation to decision of surgery was 28 minutes, from decision of surgery to transfer to operating room was 426 minutes, from arrival in operating room to anesthesia consultation was 18 minutes, and from anesthesia consultation to start of surgical incision was 75 minutes. The total average waiting time from arrival at emergency department to the start of surgery was 717 minutes. The factors were, viz., pre-occupancy of theatre (59.8%), special procedures/intervention required prior to surgery (23.9%), arrangement of logistics/finances by patient family (13%), arrangement of blood products (10.9%), consultations (9.8%), delay in giving consent by patients/family (5.4%), delay in arrangement of supplies (9.8%), and shift change of nursing staff (3.3%). Conclusion: This study shows that various preventable factors increases waiting times for emergency surgeries that should be minimized so that waiting times can be reduced. Journal of Society of Anesthesiologists 2014 1(1): 7-12